ANALISIS PENGARUH PERUBAHAN PERMENDAGRI NO. 76 TAHUN 2012 MENJADI PERMENDAGRI NO. 141 TAHUN 2017 PADA DATUM VERTIKAL DALAM PENETAPAN BATAS WILAYAH LAUT DAERAH - Eka Djunarsjah; Sendy Brammadi; Dwi Wisayantono (Universitas Pendidikan Indonesia (UPI), 2023)
A boundary is a mark that separates adjacent geographical areas and serves as a separator for the authority to manage government administration between regions and can be found on land and sea areas. Various regulations have been made by the Indonesian government to regulate regional boundaries including maritime boundaries, including Permendagri No. 76/2012 which was later amended to Permendagri No. 141/2017. This change is motivated by the fact that Permendagri No. 76/2012 is considered not in accordance with the development of the situation, so it needs to be replaced with a new ministerial regulation. One of the differences in the two Ministerial Regulations is the difference in vertical datum or height reference at the base point used as a reference for drawing the shoreline. According to Permendagri No. 76/2012, the shoreline drawing reference uses the lowest low tide level, while Permendagri No. 141/2017 uses a reference at the highest tide level. This research aims to determine the effect of vertical datum on shoreline changes in the affirmation of marine boundaries through literature study and spatial analysis. The results of this study indicate that changes in vertical datum have an influence on shoreline shifts which are also influenced by the slope of the coastal slope, shoreline shifts that drift towards the mainland cause a reduction in the area and management of regional seas.Keywords:Â Â Analysis, Maritime Boundary, Regional Boundary, Slope, Vertical Datum